A Revision of the Relationship between Gambling Disorder, Attention Deficit Hyperactivity Disorder and Parkinson´s Disease - Quintero Garzola, Gabriel C. (Pensando Psicología, 2017)
Purpose: For the present review, publications in the field of gambling disorder that deal with its relationships with others, mainly attention deficit hyperactivity disorder (ADHD) and Parkinson’s disease (PD) were consulted. Methods: The current revision includes a total of 63 references published between 1987 and 2017. It included human studies and revisions regarding the comorbidity of gambling disorder with ADHD or PD. The search terms included: gambling disorder, gambling disorder comorbidity, gambling disorder and adhd, gambling disorder and pd, gambling disorder and impulsivity. The present review focused on the link among gambling disorder and ADHD or PD, because there were a large number of publications related to these disorders. For organization purpose the current work was split into two main parts: 1) Revision of previous scientific reviews about gambling disorder, and 2) Overview and conclusions of experimental work about gambling disorder. Conclusions: The principal conclusions of the current review are: 1) subjects with a gambling disorder have a higher incidence of ADHD(and also of attention deficit disorder [ADD]), 2) the presence of ADHD in subjects that suffer of gambling disorder implies more challenges for the health care system, and 3) PD treatments that increase the agonism of dopamine type of receptor are related to an elevated probability for developing a gambling problem or an impulse control disorder.